Serial negative response after standard and third (Booster) dose of COVID-19 inactivated vaccine is associated with low vitamin D levels in patients with solid cancers - Ma, Yifei; Zhu, Pengfei; Zhong, Guanqing; Wang, Dao; Cao, Lu; Bai, Shenrui; Wang, Youlong; Zhang, Ao; Wang, Xinjia (Frontiers in Medicine, 2022)
Introduction The response is poorly understood to the third dose in cancer patients who failed the standard dose of inactivated SARS-CoV-2 vaccines (CoronaVac). We aim to assess the immune response to the third dose and identify whether vitamin D deficiency is associated with serial serologic failure in cancer patients. Methods Solid cancer patients (SCP-N) and healthy controls (HC) who were seronegative after the standard-dose vaccines in our previous study were prospectively recruited, from October 2021 to February 2022, to receive the third dose vaccines and anti-SARS-CoV-2S antibodies were measured. SCP-N who failed the third dose (serial seronegative group, SSG) were matched by propensity scores with the historical standard-dose positive cancer patient group (robust response group, RRG). An exploratory analysis was carried out to validate the role of vitamin D on the serology response. Results The multi-center study recruited 97 SCP-N with 279 positive controls as RRG and 82 negative controls as HC group. The seroconversion rate after third-dose vaccination was higher in SCP-N than in HC (70.6% vs. 29.4%, p<0.01). Matched comparison showed that SSG patients had a significantly lower level of vitamin D and consumption rate than RRG or RRG-B (RRG with third-dose positive) (all p<0.01). None had serious (over grade II) adverse events after the third dose. Conclusions SCP-N may have a relatively poor humoral response to the third dose of vaccines as compared to the seronegative HC group. The consecutively poor humoral response could be associated with poor vitamin D levels and intake. Vitamin D status and cancer-related immune compromise may jointly affect the humoral response following booster vaccination.